2009
DOI: 10.1021/jp809806w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosoluble Cyclodextrin/Poloxamer Polypseudorotaxanes at the Air/Water Interface, in Bulk Solution, and in the Gel State

Abstract: The interactions between poloxamer 407 (Pluronic F127, PF127) and two hydrophilic derivatives of beta-cyclodextrin, i.e., hydroxypropyl-beta-cyclodextrin (HPbetaCD; molar substitution (MS) 0.65) and methylated-beta-cyclodextrin (MbetaCD; MS 0.57), were characterized by means of surface tension measurements, pi-A isotherms, isoperibol microcalorimetry, 1H NMR, and rheometry. An effective complexation of poloxamer with the two CDs was evidenced as a change in the surface pressure of the pi-A isotherm of PF127 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 54 publications
5
38
0
Order By: Relevance
“…However, the surface tension of water decreased to 65.3±0.2 mN/m in presence of HPCD. This value is in agreement to those reported by Leclercq [37] and Nogueiras-Nieto [38], which pointed out that some modified CDs provoke a decrease in surface tension in a different way compared from typical surfactants. We have found that although there was no change in surface tension of Btz or βCD solutions, the inclusion complex showed a lower value.…”
Section: Resultssupporting
confidence: 93%
“…However, the surface tension of water decreased to 65.3±0.2 mN/m in presence of HPCD. This value is in agreement to those reported by Leclercq [37] and Nogueiras-Nieto [38], which pointed out that some modified CDs provoke a decrease in surface tension in a different way compared from typical surfactants. We have found that although there was no change in surface tension of Btz or βCD solutions, the inclusion complex showed a lower value.…”
Section: Resultssupporting
confidence: 93%
“…MO is a dye with a strong absorbance in the visible region of the spectrum, sensitive to the nature of the microenvironment in which it is present, 29 such as micelles and cyclodextrins. 11,29 The absorbance spectra of MO in water, DIMEB, and F127 ( Figure 1A, (1À3)) reveals a strong solvatochromism. In each case, the spectral contour of the main band can be fitted to a sum of two Gaussians (Supporting Information Figure SI 2).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we do not rule out that, under specific conditions (concentration, CD/ polymer ratio, etc), inclusion complexes are indeed formed once easier access to the polymer chains has been established by unimer formation, in agreement with other studies. 11,12,36 However, IC formation cannot be the cause of micellar breakup due to the extremely fast kinetics of the process revealed by these TR-SANS experiments. Slow time evolution of the structures has also been recently reported 36 and obtained by quenching of the samples below the CMT.…”
Section: Discussionmentioning
confidence: 97%
“…This fact can be explained by the formation of supramolecular assemblies named polypseudorotaxanes in which the PPO blocks are inserted in the cyclodextrin cavities [22]. As a consequence, the copolymer unimers involved in the supramolecular structure find that it is difficult to form micelles.…”
Section: Resultsmentioning
confidence: 99%